Determinants of student nurses' self-assessed TB/HIV coinfection care skill-competence in Accra, Ghana - Eric Tornu; Gladys Dzansi; Anita Fafa Dartey; Margaret Lartey (Elsevier, 2020)
Background: Graduating student nurses as the future workforce are expected to possess the requisite skill-competence to care for TB/HIV coinfected patients. However, few studies have investigated the self-assessed TB/HIV coinfection care skill-competence of graduating student nurses and its determinants in Accra, Ghana. Purpose: This study investigated final year student nurses' self-assessed TB/HIV coinfection care skill-competence and its determinants. Methods: This was a descriptive cross-sectional survey among Bachelor of Science in nursing (n = 112) and Diploma in nursing (n = 236) students in their final year of training in four (4) nursing training institutions using convenience sampling technique. Descriptive, independent t and Kruskal Wallis mean rank statistical tests were conducted to identify determinants. Results: TB/HIV coinfection care skill-competencies were low. Determinants of TB/HIV coinfection care skill-competence were age (r = 0.110, p = .048), duration of managing patients (r = 0.219, p = .005) and ownership of nursing training institution (p = .005). Other factors included student nurses' previous experience working in a TB health facility (p < .001), previous experience managing TB/HIV coinfection patients (p = .001), students' level of education (p = .026), speciality in nursing (p = .013) as well as awareness of the World Health Organization's taskshifting guidelines for HIV care (p < .001). Conclusions: Student nurses still have skill-competence gaps in TB/HIV coinfection care. They may not be fully skilled to independently deliver health services to TB/HIV coinfected patients per World Health Organization taskshifting guidelines. Additional training and supervision prior to deployment is required.